Rare case of glandular odontogenic cyst in the posterior mandibular ramus: A case report - Nasem Jamal Yousef; Issa Saad; Marwan Al-Raeei; Chadi Azmeh; Maya Saad; Zeina Darwich; Maya Jokhadar; Ammar Nasser Agha; Waad Omran; Thayer Marouf (Oral Oncology Reports)
The glandular odontogenic cyst is a rare developmental cyst with odontogenic origins that shares similarities with other odontogenic lesions. While generally considered benign, GOCs can exhibit aggressive behavior and may transform into more aggressive lesions like ameloblastoma or mucoepidermoid carcinoma. Therefore, it is crucial to closely monitor and follow up after treatment. With less than 200 reported cases in the literature, GOCs are important due to their propensity for recurrence and potential confusion with other lesions. Oral and maxillofacial radiologists play a key role in diagnosing GOC, given its complex histopathology. In this particular case, a 14-year-old male presented with a well-defined radiolucent lesion in his posterior mandibular ramus, making it the third reported case of GOC in Syria. The discovery of the lesion was incidental, as it was found during a routine panoramic view. The radiolucent lesion extended from the distal border and apex of the lower right first premolar into the ramus, indicating the need for thorough diagnostic evaluation and proper management of the condition. This case report emphasizes the importance of recognizing and addressing such lesions early on to prevent any potential complications. As GOCs can be locally aggressive and have a tendency to recur, timely diagnosis and appropriate treatment are crucial in ensuring the best possible outcome for the patient. Further studies and research are needed to better understand the characteristics and behavior of GOCs in the mandibular ramus region.